High carbon losses from oxygen‐limited soils challenge biogeochemical theory and model assumptions. (12th September 2021) - Huang, Wenjuan; Wang, Kefeng; Ye, Chenglong; Hockaday, William C.; Wang, Gangsheng; Hall, Steven J.
Abstract: Oxygen (O2 ) limitation contributes to persistence of large carbon (C) stocks in saturated soils. However, many soils experience spatiotemporal O2  fluctuations impacted by climate and land‐use change, and O2 ‐mediated climate feedbacks from soil greenhouse gas emissions remain poorly constrained. Current theory and models posit that anoxia uniformly suppresses carbon (C) decomposition. Here we show that periodic anoxia may sustain or even stimulate decomposition over weeks to months in two disparate soils by increasing turnover and/or size of fast‐cycling C pools relative to static oxic conditions, and by sustaining decomposition of reduced organic molecules. Cumulative C losses did not decrease consistently as cumulative O2 exposure decreased. After >1 year, soils anoxic for 75% of the time had similar C losses as the oxic control but nearly threefold greater climate impact on a CO2 ‐equivalent basis (20‐year timescale) due to high methane (CH4 ) emission. A mechanistic model incorporating current theory closely reproduced oxic control results but systematically underestimated C losses under O2  fluctuations. Using a model‐experiment integration (ModEx) approach, we found that models were improved by varying microbial maintenance respiration and the fraction of CH4 production in total C mineralization as a function of O2 availability. Consistent with thermodynamic expectations, the calibrated models predicted lower microbial C‐use efficiency with increasing anoxic duration in one soil; in the other soil, dynamic organo‐mineral interactions implied by our empirical data but not represented in the model may have obscured this relationship. In both soils, the updated model was better able to capture transient spikes in C mineralization that occurred following anoxic–oxic transitions, where decomposition from the fluctuating‐O2 treatments greatly exceeded the control. Overall, our data‐model comparison indicates that incorporating emergent biogeochemical properties of soil O2 variability will be critical for effectively modeling C‐climate feedbacks in humid ecosystems. Abstract : Traditional understanding of depressed soil C decomposition with decreasing O2 availability implies that periodic O2 deprivation should decrease both total C losses and climate impact on a CO2 ‐equivalent basis. We showed that decomposition rates of slow‐cycling C pools decreased as O2 availability declined, but oxic/anoxic fluctuations increased either the decomposition rate or amount of fast‐cycling C. Periodic anoxia may sustain C decomposition and potentially increase its climate impact over weeks to months.